Piezometric variation of the water table in the the Municipality of El- Oued, south-east Algeria - Brahim, Zine; Zaiz, Issam (جامعة الوادي - university of el oued, 2017)
Municipality of El-Oued has been confronted with the phenomenon of the upwelling of water for several years and without almost any cease to become more extensive each year. This phenomenon took very alarming dimensions the last twenty years. The use of the deep layers water (the Continental intercalary and the Final Complex) in an excessive way considerably increased the volume of the water input, as well as the absence of a natural discharge system for the rejections of wastewater, are the principal causes of this ecological imbalance. Contributing to the deterioration of the palm trees, the inundation of (Ghouts) causes mortal consequences at the level of environment, agriculture, the economy and the health of Municipality of El-Oued. The piezometric variation of the water table has shown that in the areas of upwelling groundwater; correspond to piezometric depressions which has favored the accumulation and especially of the waste water.
Article Article
Keywords: Piezometric Variation, Water Table, El-Oued, Depressions.